Faithful Translators : Authorship, Gender, and Religion in Early Modern England - Goodrich, Jaime, 1978- (Book collections on Project MUSE., 2014)
With Faithful Translators Jaime Goodrich offers the first in-depth examination of women's devotional translations and of religious translations in general within early modern England. Placing female translators such as Queen Elizabeth I and Mary Sidney Herbert, Countess of Pembroke, alongside their male counterparts, such as Sir Thomas More and Sir Philip Sidney, Goodrich argues that both male and female translators constructed authorial poses that allowed their works to serve four distinct cultural functions: creating privacy, spreading propaganda, providing counsel, and representing religious groups. Ultimately, Faithful Translators calls for a reconsideration of the apparent simplicity of "faithful" translations and aims to reconfigure perceptions of early modern authorship, translation, and women writers.